Bioavailability of the ferulic acid-derived phenolic compounds of a rice bran enzymatic extract and their activity against superoxide production. Issue 6 (19th May 2017) - Perez-Ternero, Cristina; Macià, Alba; de Sotomayor, Maria Alvarez; Parrado, Juan; Motilva, Maria-Jose; Herrera, Maria-Dolores
Abstract : Rice bran is an exceptional source of such antioxidant molecules as γ-oryzanol and ferulic acid, but their bioavailability and metabolism within this matrix remain unknown. Abstract : Rice bran is an exceptional source of such antioxidant molecules as γ-oryzanol and ferulic acid, but their bioavailability and metabolism within this matrix remain unknown. The aims of this work were to describe the oral bioavailability and metabolic pathways of the ferulic acid-derived phenolic compounds contained in a rice bran enzymatic extract (RBEE), and to determine its effect on NADPH oxidase activity. Wistar rats were administered with RBEE and sacrificed at different times over a period of 24 h to obtain plasma. An additional group was used for collection of urine and faeces over a period of 48 h. The phenolic metabolites were determined by ultra-performance liquid chromatography coupled to tandem mass spectrometry (UPLC-MS/MS), and plasma pharmacokinetic parameters were calculated. In parallel, aortic rings were incubated in the plasma of rats sacrificed 30 min after RBEE gavage, or in the presence of RBEE, ferulic acid or γ-oryzanol. Endothelin-1-induced superoxide production was recorded by lucigenin-enhanced luminescence. Twenty-five ferulic acid metabolites showing biphasic behaviour were found in the plasma, most of which were found in the urine as well, while in the faeces, colonic metabolism led to simpler phenolic compounds. Superoxide production was abrogated by phenolic compound-enriched plasma and by RBEE and ferulic acid, thus showing the biological potential of RBEE as a nutraceutical ingredient.